A bibliographic survey on Baba literature: Focus on Chinese literary translated works into Baba Malay / Yoong Suan Kui - Yoong , Suan Kui (2001)
This study analyses the Baba translated works between 1889-1950, focussing on 68 unique titles identified from six libraries: University of Malaya Library, and the libraries at Dewan Bahasa dan Pustaka. University Science of Malaysia, National Library of Singapore, National University of Singapore and the British Library. The Baba translated works indicated three periods of publication productivity between 1889-1909 (the embryonic period), which produced 18 publications, between 1910- 1929 (the stagnant period) with 10 titles and between 1930-1939 (the revival period) with 39 titles. One title was published in 1950. The main focus of the study is on the translator. Between 1889 to 1950, 11 persons were involved and the most prominent translator between 1889-1909 was Chan Kim Boon (6 titles). Between 1910-1929, 6 persons were active, and between 1930-1939, 14 persons were involved. In general, Wan Boon Seng was the most active with 22 titles, followed by Seow Chin San with 10 titles and Lee Seng Poh with 8 titles. Some of the translators were also editors and used Chinese and romanised Malay readers to help relate orally the Chinese classical stories. There were thirty two publishers and twenty one printers involved in the production of the Baba translated works. All the publishers were located in Singapore. The most active was Wan Boon Seng, Kim Seck Chye Press and Nanyang Romanized Malay Book co. The most active printers were Khai Seng Press, Tak Seng Press and Kim Seck Chye Press. The translated works basically cover historical stories (24 titles), chivalrous stories (18 titles), romances (10 titles), folklore (9 titles) and legends (7 titles). The titles were priced between 10 cents to 2 dollars in Straits currency. The sizes of the books were between 16cm x 10cm to 19cm x 14cm. The University of Malaya Library holds the largest number of collection (61 titles) of which 15 titles were not held by the other libraries. This is followed by the National Library of Singapore (24 titles), University Science of Malaysia (22 titles), Dewan Bahasa and Pustaka (20 titles), National University of Singapore (16 titles) and the British Library (9 titles). This study describes the Chinese Peranakan literary contributions in the early years and highlights their contribution in enriching Malaysia's national literary heritage. It also reveals the incompleteness of the Baba translated works collection in all six libraries studied.